2010
DOI: 10.1586/erd.10.5
|View full text |Cite
|
Sign up to set email alerts
|

Drug-eluting balloon: new tool in the box

Abstract: Percutaneous coronary intervention has revolutionized coronary revascularization therapy. It is increasingly becoming an attractive alternative to medical therapy and surgical revascularization in the treatment of coronary artery disease. Restenosis is a major challenge, and has been described as the Achilles heel of the procedure. It is a serious occurrence that can lead not only to recurrent angina and repeat revascularization, but also to acute coronary syndromes. Newer devices and strategies are being cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 60 publications
0
4
0
1
Order By: Relevance
“…In a review of 5783 reports identified for the drug-eluting stents in the United States Food and Drug Administration database, Nebeker et al found 262 unique events with hypersensitivity symptoms, of which one (0.02%) was certainly and nine (0.15%) probably caused by the drug-eluting stents (24). We also do not know whether drug-eluting devices may cause long-term 'adverse positive remodelling', which may lead to arterial ectasia or aneurysm formation (25,26). The cost-effectiveness of drug-eluting balloons are also under intense scrutiny, as they are designed for single-inflation only, and some calcified, long, or locally dissected lesions may require multiple inflations requiring multiple drug-eluting balloons, thus amounting to the increased cost of the procedure (27).…”
Section: Resultsmentioning
confidence: 99%
“…In a review of 5783 reports identified for the drug-eluting stents in the United States Food and Drug Administration database, Nebeker et al found 262 unique events with hypersensitivity symptoms, of which one (0.02%) was certainly and nine (0.15%) probably caused by the drug-eluting stents (24). We also do not know whether drug-eluting devices may cause long-term 'adverse positive remodelling', which may lead to arterial ectasia or aneurysm formation (25,26). The cost-effectiveness of drug-eluting balloons are also under intense scrutiny, as they are designed for single-inflation only, and some calcified, long, or locally dissected lesions may require multiple inflations requiring multiple drug-eluting balloons, thus amounting to the increased cost of the procedure (27).…”
Section: Resultsmentioning
confidence: 99%
“…The other possible solution to fight re-stenosis in the BTK district could be Drug eluting balloons. This new technology, Paclitaxel-coated balloons should be a potential role in the peripheral district (Manzi M, et al 2010;Sharma S, et al 2010;Waksman P, et al 2009) to avoid re-stenosis due to the antiproliferative effect. The use of DEB is not technically complex and there are, actually, a wide range of different devices.…”
Section: Deb'smentioning
confidence: 99%
“…Balony uwalniające lek antymitotyczny (drug eluting balloon, DEB) to potencjalna alternatywa dla stentów uwalniających lek antymitotyczny lub uzupełnienie dla BMS [18]. Obecnie dostępne na rynku DEB (uwalniające paklitaksel) to DIOR, Elutax, SeQuent™ i IN.PACT™ Falcon.…”
Section: Balony Uwalniające Lek Antymitotycznyunclassified